2019
DOI: 10.1093/ofid/ofz360.418
|View full text |Cite
|
Sign up to set email alerts
|

345. Acute Onset Diabetic Ketoacidosis/Hyperosmolar Hyperglycemic State in Patients Taking Integrase Strand Transfer Inhibitors

Abstract: BackgroundA few case reports have noted uncontrolled hyperglycemia in patients switched to dolutegravir. Several cohort studies have found increased weight gain among patients treated with integrase inhibitors (INSTI). We present clinical observations among 3 patients admitted to hospital for diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS) while receiving INSTIs for the management of HIV.MethodsCase 1: A 44-year-old man with HIV and dyslipidemia presented with altered mental status and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Recent case reports have also documented the development of accelerated hyperglycemia and DKA after initiation of these therapies. In One case series, 3 patients developed DKA while on DTG- or elvitegravir-based regimens [ 12 ]. However, 2 of the 3 reported patients developed diabetes more than 1 year after starting an INSTI-based regimen, making the association with ART therapy less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent case reports have also documented the development of accelerated hyperglycemia and DKA after initiation of these therapies. In One case series, 3 patients developed DKA while on DTG- or elvitegravir-based regimens [ 12 ]. However, 2 of the 3 reported patients developed diabetes more than 1 year after starting an INSTI-based regimen, making the association with ART therapy less clear.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recently, there is mounting evidence that INSTIs cause deranged glucose metabolism. [8][9][10][11][12][13][14][15][16][17] Severe a potential and noticed side effect of the DTG-based ART regimen. Baseline and periodic monitoring of plasma glucose might be required in ART regimens containing dolutegravir.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been a few documented reports on deranged glucose metabolism with integrase strand transfer inhibitors (INSTIs) use. [8][9][10][11][12][13][14][15][16][17] SAILING, SPRING-2, SINGLE and VIKING-3 clinical trials reported the incidence of moderate (plasma glucose, 126-250 mg/dl) and severe hyperglycemia (plasma glucose, >250 mg/dl) were 6-9% and 1-2%, respectively, after INSTIs therapy. [8][9][10][11] This case series is the first of its kind in Ethiopia to report on new onset diabetes mellitus after dolutegravir-based ART use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multivariable analysis, patients with prior DTG use had seven times greater odds of subsequent diagnosis of hyperglycemia compared to those who had non-DTG-based regimens (adjusted odds ratio [aOR] 7.01, 95% CI 1.96-25.09). The odds of hyperglycemia also increased with age (56 years and above vs. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] aOR 12.38,) and hypertension (aOR 5.78,). Our study demonstrates a strong association between prior DTG exposure and subsequent diagnosis of hyperglycemia.…”
mentioning
confidence: 99%